Incidencia de la politica de inversión en la gestión económica y financiera de la empresa agroindustrial Laredo S.A.A., período 2014-2015 - Lezcano Gutierrez, Meissy Almendra (2017)
The research is related to the investment policy and its incidence. Its purpose is to determine the impact of the investment policy on the economic and financial management of the company Agroindustrial Laredo S.A.A. Period 2014 - 2015. This research has as population the Agroindustrial Company Laredo S.A.A. The sample is represented by Empresa Agroindustrial Laredo S.A.A The research design is non-experimental, because the research variables are not manipulated and it is cross-sectional because the information that was taken is specific time periods. Mainly the company makes investments in land, machinery and equipment, it invests to obtain some future economic benefit or added value for the shareholders. It makes investment decisions and evaluates its investment projects taking into account its established criteria. It can be concluded that the research company used some investment policies in an empirical way, showing deficiencies in its economic and financial management. It was recommended to clearly define procedures for evaluating investments and establishing well-structured investment policies.